Peningkatan Kinerja Karyawan Perbankan Syariah di Gorontalo (Studi atas Budaya Organisasi, Kompetensi dan Motivasi) - Mustofa Mustofa (Al-Ulum, 2017)
The purpose of this article is to analyse the influence of organizational culture and competence to motivation; organizational culture and competence directly on performance; motivation on performance; and organizational culture and competence on employee performance through employee motivation of syariah banks in Gorontalo. The result shows that organizational culture and competence have a positive and significant effect on motivation organizational culture has a positive and significant impact on employee performance. while the competence does not significantly affect the performance of employees; Motivation has a positive and significant impact on performance; And organizational culture and competence have a positive and significant effect on employee performance through motivation. This study recommends that further research on the same substance in the wider scope in the other organization level must be taken into account in order to obtain a more comprehensive picture of the development of contribution of organizational culture role and competence to motivation and performance of sharia banking employees, and leadership of sharia banking.